A series of homonuclear lanthanide coordination polymers based on a fluorescent conjugated ligand: syntheses, luminescence and sensor for pollutant chromate anion. Issue 41 (25th September 2015) - Feng, Xun; Li, Rongfang; Wang, Liya; Ng, Seik Weng; Qin, Guozhan; Ma, Lufang
Abstract : Series of homonuclear lanthanide coordination polymers incorporating conjugated ligand have been fabricated successfully and characterized systematically. Abstract : A family of six new homo-lanthanide coordination polymers incorporating a conjugated ligand of 2, 5-di(2′, 4′-dicarboxylpheny)pyridine, namely, {[Ce(μ3− ddpp)]·4H2 O} n (1 ), {[Nd(μ3− ddpp)]·2H2 O} n (2 ), {[Sm(μ6− ddpp)]·H2 O}·H2 O} n (3 ), {[Eu(μ6− ddpp)]·H2 O} n (4 ), {[Tb(μ6− ddpp)]·H2 O} n (5 ), and {[Er(μ6− ddpp)]·H2 O} n (6 ) (H3 ddpp = 2, 5-di(2′, 4′-dicarboxylpheny)pyridine acid), has been prepared successfully through solvothermal reactions. Polymers1–6 exhibit various coordination environments and different multi-dimensions, but they are all assembled in a one dimensional (1-D) Ln–carboxylate chain. Polymer1 only shows a 1-D ribbon chain, while polymer2 exhibits a binodal (3, 8)-connected topology net. Heavy lanthanide polymers4–6 possess 3D frameworks based on a rare (4, 8)-connectedmsw framework. Thermogravimetric and different thermal analysis measurements indicate that they all display high thermal stability. The luminescence emission spectra display characteristic f–f transition emissions of Ln(iii ) polymers in visible or near infrared (NIR) regions. The fluorescent ligand H2 ddpp provides efficient energy transfer for the sensitization of Eu(iii ) and Tb(iii ) ions in the visible region, among which a Tb(iii ) polymer may be employed as a fluorescence ratiometric probe for the pollutant CrO4 2− anion.